Hubungan Pemberian Insentif dan Motivasi Kerja dengan Kinerja Karyawan di Rumah Sakit Pertamedika Ummi Rosnati (RSPUR) Banda Aceh - Wiki Noviandi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to determine how incentives and compensation affect employee performance. The sample in this study was 78 people who work at Pertamedika Ummi Rosnati Hospital. This study is a survey study with a quantitative approach, using multiple linear regression analysis methods with the help of the SPSS program. The results of this study indicate that incentives (X_1) have a positive effect and a significant level below 0.05, namely (0.036 <0.05) or H_(a) is accepted on employee performance (Y) at Pertamedika Ummi Rosnati Hospital partially (tcount value> ttable or 2.136> 1.664). Compensation (X_2) has a positive influence and a significant level below 0.05, namely (0.000 <0.05) or H_(a) is accepted on employee performance (Y) at Pertamedika Ummi Rosnati Hospital partially (tcount value> ttable or 5.120> 1.664). The variable with the most dominant influence on employee performance (Y) at Pertamedika Ummi Rosnati Hospital is the compensation variable (X_2) with a tcount value> ttable or 5.120> 1.664 and the smallest significant value of 0.00. The results of the F test show that the incentive variables (X_1) and compensation (X_2) together have a positive and significant effect on employee performance (Y) at Pertamedika Ummi Rosnati Hospital. Based on the results of the study, the author suggests that employee welfare can be improved and the allowance nominal that has been implemented can be maintained so that the quality of employee work is better at Pertamedika Ummi Rosnati Hospital.